Understanding the psychological pathways from ocean literacy to pro-environmental behavior: the mediating roles of marine responsibility and values - Wang, Linzhao; Gao, Tao; Shi, Yanjie; Zhang, Li (Frontiers in Psychology, 2025)
IntroductionThis study investigates the psychological mechanisms underlying the relationship between ocean literacy and pro-environmental behavior, with a particular focus on the mediating roles of marine environmental responsibility and marine values.MethodsA large-scale survey was conducted with 1,206 university students from 23 universities across 11 provinces in China. Standardized and validated questionnaires were administered, and advanced statistical analyses, including structural equation modeling and mediation analysis, were employed to examine the hypothesized relationships.ResultsFindings reveal that ocean literacy significantly enhances individuals’ sense of environmental responsibility and fosters stronger pro-environmental values. These psychological constructs, in turn, contribute to increased engagement in conservation behaviors, such as reducing plastic use and participating in beach clean-ups.DiscussionGrounded in theoretical frameworks from environmental psychology—namely the Value-Belief-Norm Theory and the Theory of Planned Behavior—this study underscores the importance of integrating cognitive, affective, and normative factors in promoting sustainable marine actions. The results offer valuable insights for the design of educational interventions and behavioral strategies aimed at advancing marine conservation efforts.